2001
DOI: 10.1146/annurev.earth.29.1.331
|View full text |Cite
|
Sign up to set email alerts
|

The Late Ordovician Mass Extinction

Abstract: ▪ Abstract  Near the end of the Late Ordovician, in the first of five mass extinctions in the Phanerozoic, about 85% of marine species died. The cause was a brief glacial interval that produced two pulses of extinction. The first pulse was at the beginning of the glaciation, when sea-level decline drained epicontinental seaways, produced a harsh climate in low and mid-latitudes, and initiated active, deep-oceanic currents that aerated the deep oceans and brought nutrients and possibly toxic material up from oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
264
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(280 citation statements)
references
References 65 publications
5
264
0
1
Order By: Relevance
“…The late Ordovician mass extinction has been related to a period of rapid cooling followed by a period of rapid global warming (Orth et al 1986;Brenchley et al 1994Brenchley et al , 1995Brenchley et al , 2003. Brenchley (1984), Brenchley et al (1991Brenchley et al ( , 1994Brenchley et al ( , 1995Brenchley et al ( , 2003, Briggs et al (1988), Owen et al (1991), Fortey & Cocks (2003), Sheehan (2001) and others have convincingly demonstrated how global cooling and warming events could have led to a mass extinction, and we do not dispute the contribution of global cooling to this extinction.…”
Section: Aspects Of the Late Ordovician Mass Extinction Potentially Cmentioning
confidence: 50%
See 2 more Smart Citations
“…The late Ordovician mass extinction has been related to a period of rapid cooling followed by a period of rapid global warming (Orth et al 1986;Brenchley et al 1994Brenchley et al , 1995Brenchley et al , 2003. Brenchley (1984), Brenchley et al (1991Brenchley et al ( , 1994Brenchley et al ( , 1995Brenchley et al ( , 2003, Briggs et al (1988), Owen et al (1991), Fortey & Cocks (2003), Sheehan (2001) and others have convincingly demonstrated how global cooling and warming events could have led to a mass extinction, and we do not dispute the contribution of global cooling to this extinction.…”
Section: Aspects Of the Late Ordovician Mass Extinction Potentially Cmentioning
confidence: 50%
“…Prior to the late Ordovician cooling, temperatures were relatively warm and it is the suddenness of the climate changes and the elimination of habitats due to sea-level fall that are believed to have precipitated the extinctions (Brenchley et al 1991(Brenchley et al , 1994(Brenchley et al ,1995(Brenchley et al , 2003Melchin & Mitchell 1991;Owen et al 1991;Sheehan 2001). We emphasize that there is evidence for a possible link between GRBs and global cooling.…”
Section: Aspects Of the Late Ordovician Mass Extinction Potentially Cmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, the beginning of the Cambrian Period (and simultaneously of the Palaeozoic Era and the Phanerozoic Eon, or base of the Cambrian System) has been placed at the appearance of a distinctive trace fossil assemblage that reflects a change in behaviour associated with the earliest burrowing bilaterian animals (emerging during the 'Cambrian explosion' of metazoan animals), and so the beginning of an abundant fossil record within strata (Landing, 1994). To take another example, the boundary between the Ordovician and Silurian periods reflects a brief, intense glacial phase that triggered one of the 'Big Five' mass extinction events, and hence profoundly altered the biota (and fossil record) of the Earth (Sheehan, 2001). Likewise, each of the Cenozoic epochs is characterized by distinctive assemblages of fossil life, with the biotic changes that help define their boundaries being rapid relative to the constancy of the biota that lasts through each epoch .…”
Section: The International Chronostratigraphic Chart and The Anthropomentioning
confidence: 99%
“…1 (Berry, 2010;Leggett, 1980;Thickpenny and Leggett, 1987;Trela and Podhalanska, 2010;Wilde, 1987) including Poland (Melchin et al, 2013;Page et al, 2007). During the Ordovician-Silurian transition, there were considerable changes in the atmosphere, ocean, biosphere and, hence, in the general marine depositional conditions (Underwood et al, 1997) inextricably linked with the Late Ordovician (End Hirnantian) glacial event (Melchin et al, 2013;Sheehan, 2001). Glaciation events Mustafa, K.A., Sephton M.A., Spathopoulos, F., Watson, J.S., Krzywiec, P. Organic geochemical characteristics of black shales across the Ordovician-Silurian boundary in the Holy Cross Mountains, Central Poland, Marine andPetroleum Geology, doi:10.1016/j.marpetgeo.2015.08.018. 3 have major influence on the productivity and preservation of organic matter due to the changes in oceanic ventilation and circulation that cause oxygenation of the seawater (Berry and Wilde, 1978;Berry, 2010;Wilde, 1987).…”
Section: Introductionmentioning
confidence: 99%